The Application of the Paired Storytelling Model in Responding to Short Story Texts Heard Thru Audio Podcast Media in Phase F Students - Repani Julyani; Panca Pertiwi Hidayati; Eggie Nugraha (Global Action and Education for Society, 2025)
This study aims to describe the application of the Paired Storytelling model in responding to short story texts listened to thru audio podcasts and to evaluate the effectiveness of this model in improving listening skills of Phase F students at SMAN 12 Bandung. The main problem in this study is the low listening skills of students, caused by a lack of attention to the listening process and the ineffectiveness of the media and learning models used. This research uses a quantitative approach with a quasi-experimental method of the Non-Equivalent Control Group Design type. The research sample consists of two classes: the experimental class using the Paired Storytelling model and podcast media, and the control class using the conventional discussion model. Data collection techniques were carried out thru observation, attitude assessment, and pre- and post-tests. Data analysis was performed using statistical tests with the assistance of IBM SPSS Statistics 25. The research results indicate that the Paired Storytelling model using audio podcasts has a significant positive impact on improving students' listening comprehension skills. Students in the experimental class showed better learning outcomes compared to the control class, both in terms of understanding the structure and intrinsic elements of short stories. Thus, the audio podcast-assisted Paired Storytelling model is recommended as an effective and innovative learning strategy for improving literary text listening skills, particularly for short stories.